The diagnosis and differential diagnosis of Cushing's syndrome. - Newell-Price, J; Jorgensen, J; Grossman, A (1999)
Cushing's syndrome is defined as the symptoms and signs of glucocorticoid excess, but the precise diagnosis may be difficult to establish and harder to localise. The clinicial, biochemical and imaging features of the syndrome are discussed in the light of our own extensive experience and the published literature. We describe the optimal diagnostic routines currently recommended in major centres, and analyse the sensitivities and specialities of the various tests employed. Only by means of establishing a precise diagnosis can the disorder be successfully treated.